Manajemen Masjid Berbasis Keterlibatan Masyarakat Lintas Etnis pada Komunitas Tionghoa - Insani Nurul Imani; Fakhruddin, Agus (Alhadharah: Jurnal Ilmu Dakwah, 2023)
This study aims to investigate the community-based mosque management across ethnicities at Masjid Lautze 2 in Bandung City, with a specific focus on the Chinese ethnic community. In the context of Indonesia, many mosques have experienced a narrowing of roles and functions, a lack of systematic management, and exclusivity in decision-making and administration, resulting in stagnation in operational programs. This research employs a qualitative approach with a descriptive case study method to delve into this phenomenon. Data were obtained through observations, interviews, and documentation, involving key informants such as the Secretary of DKM Masjid Lautze 2, mosque officials, and mosque congregants. The findings of the research indicate that community-based mosque management across ethnicities has several significant benefits. Firstly, it allows for a better understanding of the needs and desires of the Chinese ethnic community and the surrounding society. Secondly, it strengthens social bonds between the mosque and a diverse ethnic community, creating an inclusive environment. Thirdly, it enables active contributions from various ethnicities in the mosque's development. Fourthly, it enriches the experience of diversity and religious life. This research contributes to understanding the importance of community-based mosque management across ethnicities in creating an inclusive environment and strengthening unity in religious life. These findings can serve as a guideline for other mosques to optimize their roles and functions in society, especially in the context of ethnic diversity in Indonesia.